A Study on the Effect of Hydrogen Gas Explosion in a Cylinder Cabinet for Semiconductors on the Protective Wall - Min, Mimi; Lee, Kwangho; Jung, Seungho (Energies, 2022)
In the semiconductor industry, hydrogen is used with many other hazardous and dangerous substances with flammable, toxic, and corrosive properties. In order to safely handle them, convenient-to-use gas cabinets are often required. As known well, hydrogen is highly flammable and explosive, and risk analysis needs to safely use the gas in the cabinets. In this study, overpressure and impact according to various gas cabinet conditions were measured when hydrogen leaks in the gas cabinet, and the effect of overpressure on the protective wall was simulated. For the research, a demonstration experiment was conducted by custom manufacturing a gas cylinder cabinet identical to the standard used in the field, and the protection performance analysis was performed by reverse-engineering it through 3D scanning. As a result of the demonstration experiment, the maximum pressure at the time of hydrogen gas explosion in the gas cylinder cabinet was measured at 0.3 bar. After calculating the detonation pressure propagation profile using the TNT equivalence method, the protective performance of the protective wall was confirmed using AUTODYN. The maximum stress of the concrete and the maximum stress of the reinforcing bar due to the explosion in the gas cylinder cabinet were calculated to be 30.211 MPa and 112.88 MPa, respectively, which do not exceed the tensile strength of concrete and the yield strength of the reinforcing bar. This result is expected to be of great help to the development of the semiconductor industry by suggesting the rationale for mitigating the firewall when changing the semiconductor layout.
Keywords: 3d AUTODYN; AUTODYN; Gas cabinets; Gas cylinder cabinet; Gas explosions; Gas protective wall; Hydrogen gas; Maximum stress; Overpressure; Semiconductor industry; 3D AUTODYN; explosion; gas cylinder cabinet; gas protective wall; hydrogen gas